Bovine genital leptospirosis: Findings in bulls maintained in Caatinga biome conditions - Barnabé, Nathanael N.C.; Soares, Rafael R.; Nogueira, Denise B.; Araújo Júnior, João P. [UNESP]; Malossi, Camila D. [UNESP]; Costa, Diego F.; Silva, Maria L.C.R.; Higino, Severino S.S.; Azevedo, Sérgio S.; Alves, Clebert J. (FapUNIFESP (SciELO), 2023)
Leptospirosis is a disease that causes economic and social impact, as it affects wild and domestic animals and humans. There may be peculiarities in the epidemiology of this disease in the Caatinga biome, Brazil, where the environment is adverse and the etiologic agent, Leptospira spp., requires alternative transmission routes. Considering that in bovine leptospirosis the genital carrier is constantly neglected and the lack of reports on the role of bulls in the epidemiology of the bovine genital leptospirosis (BGL) syndrome, mainly in semiarid conditions such as Caatinga biome, this study aimed to investigate bulls maintained in Caatinga biome conditions as genital carriers of leptospires. Urinary tract (urine, bladder, and kidney) and reproductive tract (vas deferens, cauda epididymis, and vesicular gland) samples were collected from 42 slaughtered bulls. Microscopic agglutination test (MAT), polymerase chain reaction (PCR), and microbiological isolation were included as diagnostic methods. Anti-Leptospira spp. antibodies were found in 17 (40.48%) animals, while 26 animals (61.90%) had at least one organ or urine with leptospiral DNA, and 10 animals (23.81%) were positive at bacteriological culture. Sequenced samples targeting the LipL 32 gene showed 99% similarity with Leptospira borgpetersenii. Molecular analysis of samples from the vas deferens and cauda epididymis is recommended for the diagnosis of genital leptospirosis in bulls and, if it is impossible to collect these tissues, semen can be used. In conclusion, this study provides important information relating to bulls from the Caatinga biome, Brazil, as carriers of genital leptospirosis. The results indicate that, even under adverse environmental conditions, leptospires may survive and propagate, mainly due to the characteristic of genital carriers for the sexually spreading of adapted species without influence by external variables. Thus, prevention and control strategies for bovine leptospirosis need to include actions aimed at the genital carrier.
Keywords: bacteriological culture; bulls; Caatinga; genital carrier; Leptospira spp; PCR; semiarid